2014
DOI: 10.1002/btpr.1993
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced fermentative capacity of yeasts engineered in storage carbohydrate metabolism

Abstract: During yeast biomass production, cells are grown through several batch and fed-batch cultures on molasses. This industrial process produces several types of stresses along the process, including thermic, osmotic, starvation, and oxidative stress. It has been shown that Saccharomyces cerevisiae strains with enhanced stress resistance present enhanced fermentative capacity of yeast biomass produced. On the other hand, storage carbohydrates have been related to several types of stress resistance in S. cerevisiae.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…That may be because neutral trehalase could be encoded by multiple genes, such as the NTH2 gene. , However, NTH1 deletion can still help slow down the trehalose degradation in B – NTH1, B – N + T, B – N + T + K, B – N + M, and B – N + T + MAL62 strains. This explains why the tripartite mutant (B – N + T + MAL62) provides the best enhancement for the freezing tolerance and improves the fermentation characteristics …”
Section: Discussionmentioning
confidence: 96%
“…That may be because neutral trehalase could be encoded by multiple genes, such as the NTH2 gene. , However, NTH1 deletion can still help slow down the trehalose degradation in B – NTH1, B – N + T, B – N + T + K, B – N + M, and B – N + T + MAL62 strains. This explains why the tripartite mutant (B – N + T + MAL62) provides the best enhancement for the freezing tolerance and improves the fermentation characteristics …”
Section: Discussionmentioning
confidence: 96%
“…In addition, we found that NHT1 deletion (B-NTH1, B-NTH1 + K and B-NTH1 + MAL62) induced a low neutral trehalase (Table 3 ), which caused a lower level of trehalose degradation. High activity of trehalose synthase (+MAL62) [ 38 ] and low activity of neutral trehalase (−NTH1) increase the intracellular trehalose level [ 26 ], which explains why the double mutant (B-NTH1 + MAL62) provides the best freezing tolerance and fermentation characteristics [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TPS1 (synthase subunit of trehalase-6-P synthase/phosphatase complex) and deletion of NTH1 (neutral trehalose) increase ethanol tolerance [17]. Besides, overexpression of GSY2 (Glycogen synthase) and NTH1 increased respectively glycogen and trehalose levels that are important for the fermentative capacity [18]. Global transcription machinery engineering (gTME) is a technique that alter key proteins to regulate the global transcriptome by error-prone polymerase chain reaction (epPCR) mutations.…”
Section: Improving Stress Tolerancementioning
confidence: 99%